Numerical and experimental investigations on fretting fatigue properties of GH4169 superalloy at the elevated temperature. (August 2021) - Wang, Jingchen; Gao, Yukui
Highlights: Rotating bending fretting fatigue properties of GH4169 were examined at 650 °C. The influences of interference magnitudes were investigated. The SWT model was extended for crack description considering the subsurface stresses. The compression load effect on crack propagation was emphasized for GH4169. Abstract: Fretting fatigue is a detrimental phenomenon in aeronautic industry, where the appropriate methods for crack location prediction and total life prediction are vital. In the present paper, both experimental and numerical approaches were developed for GH4169 superalloy with different interference magnitudes at 650 °C. Three fretting crack initiation models were compared for crack location prediction, among which the SWT model was extended to describe the initiation face in the three-dimensional model considering the subsurface stresses. Moreover, three propagation models were conducted for crack growth rate calculation. One of the methods was the combination of the linear superposition model with the Harter-T method, which emphasized the compression load effect on the driving force of crack propagation rates and the negative stress ratio variation impact. Finally, the life prediction approach was proposed using the averaged SWT parameters combined with the composite propagation model. The obtained total life estimations were found to agree well with the experimental results.